Invasion and reproduction by rootlesion nematode (Pratylenchus penetrans) differs among selected lines of red clover (Trifolium pratense) - Papadopoulos, Y.A.; Kimpinski, J.; McRae, K.B.; Christie, B.R.; Gallant, C.E.; Fillmore, S.A.E (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2002)
Eighteen cultivars and breeding lines of red clover (Trifolium pratense) were evaluated in a greenhouse study for their relative response to inoculation by the root-lesion nematode (Pratylenchus penetrans). The incidence of plants invaded and the nematode concentration in the roots were generally related but not always. One cultivar (Florex) had a low incidence of plants being invaded, but a high concentration of nematodes in the roots of invaded plants. Three entries (CRS 15, CRS 5, and CRS 11) displayed a low incidence of plants being invaded and a low concentration of nematodes in the root. One cultivar, AC Kingston, was judged to be highly susceptible, while the remaining entries had differing invasion incidences and differing concentrations of root-lesion nematodes in the roots.